The Role of NGF and Its Receptor TrKA in Patients With Erectile Dysfunction - Stabile, Anna Maria; Illiano, Ester; Pistilli, Alessandra; Rende, Mario; Trama, Francesco; Bartolini, Desiree; Zucchi, Alessandro; Costantini, Elisabetta (Frontiers in Urology, 2022)
Abstract: The aim of our study was to investigate the plasma NGF concentration, TrkA/p75NTR receptor expression on White Blood Cell (WBC), in peripheral and corpus cavernosum blood isolated from patients with erectile dys-function and metabolic syndrome (ED/MetS). This was a pilot case-control study. Inclusion criteria were:men 18-65 years with ED and MetS and healthy subjects. The first sampling was performed at the level of the cubital vein (VC). Subsequently, 20 mcg of intracavernous alprostadil was administered, and a second blood draw from the corpora cavernosa (CC) was performed once erection was achieved. Subsequently, the third blood sample was repeated at the level of the VC. We enrolled 8 case with ED/MetS and 8 control. There was no significant difference between the case and control group in terms of mean age (49.3±5.9and 53.13±8.9, respectively). The case group had a lower IIEF score compared to control group ( 14±3.2 versus 27.3±2.1; p<0.05).Decreased NGF and TrKA expression on WBC and thiols were found in the plasma of ED/MetS patients compared to control. The study showed that patients with ED/MetS had a decreased in plasma NGF and thiols concentration and they had decreased in TrKA expression on WBCs.